Media Model for Catching Baseball in Class IV at Elementary School - Annisa Tri Heriani; Eka Fitri Novitasari; Mastri Juniarto (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. The aim of this study is to develop an efficient media model that can support fourth-grade students in elementary schools to enhance their learning of baseball catching. This media model is designed to enhance their motor skills and comprehension of fundamental concepts related to baseball catching. The research methodology involves creating a media model that caters to the students' learning needs and characteristics. The primary objective is to encourage the students' active participation during the learning process and assist them in mastering the baseball catching technique using gloves covered with Velcro. The ultimate goal is to improve the baseball catching skills of fourth-grade students. Materials and methods. The research employs the ADDIE model, which includes five stages: analysis, design, model development, implementation, and evaluation. Designing a glove model for fourth-grade students requires testing and analyzing various materials and shapes to identify the optimal design that caters to the students' size and characteristics. Results. Designing a high-quality glove model is crucial for enhancing students' ability to catch baseballs with ease and ensuring maximum comfort and safety. The validity test score of 0.7 confirms the model's accuracy, while its high reliability value of 0.6 ensures consistent and dependable performance. Conclusion. The development of Velcro glove media was validated by 13 experts who strongly agreed with an average percentage of 89.3%. This glove is intended to improve baseball catching skills among students and encourage their participation in physical activities.